E-Commerce Dan Peningkatan Pemasaran Produk Usaha Kecil Menengah (UKM) (Studi Kasus Di Kabupaten Jember) - Hanikka Prasetia; Zulfidda Lillah (UNEJ e-Proceeding, 2018)
In the Industry 4.0, global trade transactions (goods / services) are carried out by utilizing information technology advancements or e-commerce media. Bank Indonesia predicts that by 2018, the value of domestic trade E-Commerce transactions will reach Rp 144 trillion. In Jember Regency, there are 4097 SMEs, but only 10% of SMEs have used E-Commerce. This study aims to: (1) analyze the existence of of the impact of using E-Commerce to improve the marketing of SME products in Jember Regency, (2) Identify the factors that cause SMEs in Jember Regency to not use E-Commerce, (3) Efforts that can conducted to optimize the utilization of E-Commerce by SMEs in Jember Regency. This study uses a descriptive approach and literature study. The object of research is the SME Actors in Jember Regency. Results and Conclusions of the study show (1) The use of E-Commerce by SMEs in Kabupaten Jember has a significant impact on increasing product marketing; (2) Factors that cause SME entrepreneurs in Jember Regency to not use E-Commerce are (a) Skill of using information technology is still low, (b) Products are marketed conventionally; (3) Efforts made to optimize the use of E-Commerce are (a) need training or workshops on "effective marketing through E-Commerce" for SMEs; (b) Optimizing local startups, (c) Increasing partnerships and collaboration between government, universities and stakeholders for Technopreneur assistance.